Ozone discolysis in lumbar disc prolapse - Charan, Rajat; Runu, Ritesh; Kumar, Animesh; Chauhan, Himanshu (International Journal of Research in Orthopaedics, 2017)
Background: Treatment of low back ache due to prolapsed intervertebral disc is still controversial. Several conservative modalities are available with varied results. Surgical discectomy may lead to failed back syndrome due to change in vertebral column anatomy and its mechanics. To prevent it, conservative means are better and Ozone discolysis is one of the nonsurgical methods. The indications and effectiveness of this condition is not well defined. The present study was done to correlate the clinical outcome of this technique. Methods: This was a prospective study conducted on 67 patients presenting with symptoms of back pain with arid without radicular symptoms. X ray and MRI were done in all cases. Then intradiscal ozone gas was given at one level from a specialized machine under C arm guidance. For evaluation Oswestry disability index and Macnab scoring system was used. Post injection patients were evaluated at 2, 6 weeks and 6 months. Results: Sixty seven patients with mean age of 47.7 years were followed up for 7.8 months. Low back pain was the commonest symptom and SLR was positive in 5.36%. The modified Macnab scoring with good and fair score improved from 16% to 89% and Oswestry disability index with minimal and moderate disability improved from 41% to 91% at end of 6 months. Seven patients had relapse of pain due to repeat disc prolapse. Conclusions: Ozone discloses is better modality of treatment for low back pain with disc bulge and early disc prolapsed.